2017
DOI: 10.1038/s41593-017-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic inhibition regulates critical-period plasticity in visual cortex and thalamus

Abstract: During critical periods of development, experience shapes cortical circuits, resulting in the acquisition of functions used throughout life. The classic example of critical-period plasticity is ocular dominance (OD) plasticity, which optimizes binocular vision but can reduce the responsiveness of the primary visual cortex (V1) to an eye providing low-grade visual input. The onset of the critical period of OD plasticity involves the maturation of inhibitory synapses within V1, specifically those containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 45 publications
8
95
2
Order By: Relevance
“…We only considered plasticity in connections from layer IV to layer II/III and within layer II/III. Therefore, we did not take into account experimentally observed OD shifts in the thalamic relay neurons [Sommeijer et al, 2017, Jaepel et al, 2017 and layer IV neurons [Gordon and Stryker, 1996]. Since these areas are upstream of layer II/III, a naive explanation could be that the shift in layer II/III is fully accounted for by the shift in the inputs to this layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only considered plasticity in connections from layer IV to layer II/III and within layer II/III. Therefore, we did not take into account experimentally observed OD shifts in the thalamic relay neurons [Sommeijer et al, 2017, Jaepel et al, 2017 and layer IV neurons [Gordon and Stryker, 1996]. Since these areas are upstream of layer II/III, a naive explanation could be that the shift in layer II/III is fully accounted for by the shift in the inputs to this layer.…”
Section: Discussionmentioning
confidence: 99%
“…A well studied example is the critical period for ocular dominance (OD) in primary visual cortex (V1). In the visual pathway, inputs from both eyes usually converge onto the same neuron for the first time in V1, although a fraction of thalamic neurons already exhibits binocularity in mice [Jaepel et al, 2017, Sommeijer et al, 2017, Jeon and Kuhlman, 2017. The extent to which a neuron's visually-evoked activity is dominated by one of the eyes is called ocular dominance (OD) and is often quantified by the ocular dominance index (ODI).…”
Section: Introductionmentioning
confidence: 99%
“…A functional study (Jaepel et al, 2017) showed that ocular dominance of thalamic axons in V1 can be altered by short-term (6-8 days) MD under plasticity-enhancing conditions in adult mice but the effect was found to be transient. Another study (Sommeijer et al, 2017) reported that 7 days of MD during the critical period can lead to an ocular dominance shift in dLGN neurons. However, these studies did not address whether long-term MD during the critical period, a manipulation that has been shown to have a long-lasting impact on the animal's visual acuity (Davis et al, 2015;Prusky and Douglas, 2003;Stephany et al, 2014), can lead to persistent changes in dLGN visual properties, including binocular integration.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of recent evidence indicates that significant binocular processing occurs in dLGN in mice (Howarth et al, 2014;Jaepel et al, 2017;Sommeijer et al, 2017) and marmosets (Zeater et al, 2015). A retrograde tracing study (Rompani et al, 2017) demonstrated that single dLGN neurons receive direct retinal inputs from both eyes, providing an anatomical substrate for binocular integration in the mouse dLGN.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the effect of visual training at the subcortical level. A study carried out on the rat's dorsal lateral geniculate nucleus (dLGN), the primary recipient of visual information, suggests that the response properties of thalamic neurons are subject to experience-dependent long-term plasticity [21,22]. Similarly, in the superior colliculus (SC), the second major target of retinal input, repetitive exposure to dimming stimuli effectively induced the LTP of developing retinotectal synapses in Xenopus tadpole [23].…”
Section: Introductionmentioning
confidence: 99%